Gender and forests: climate change, tenure, value chains and emerging issues - Colfer, C.J.P.; Basnett, B.S.; Elias, Marlène (Routledge, 2016)
Focusing particularly on tropical forests, the book presents both local case studies and global comparative studies from Africa, Asia, and Latin America, as well as the US and Europe. The studies range from personal histories of elderly American women’s attitudes toward conservation, to a combined qualitative / quantitative international comparative study on REDD+, to a longitudinal examination of oil palm and gender roles over time in Kalimantan. Issues are examined across scales, from the household to the nation state and the global arena; and reach back to the past to inform present and future considerations.